Austenite decomposition and carbon partitioning during quenching and partitioning heat treatments studied via in-situ X-ray diffraction. (15th September 2019) - Ebner, Sandra; Suppan, Clemens; Stark, Andreas; Schnitzer, Ronald; Hofer, Christina
Abstract: High strength combined with excellent ductility can be achieved by quenching and partitioning (Q&P) microstructures containing martensite and a considerable amount of retained austenite. Since the mechanical properties are inherited from the microstructure, a thorough understanding of this relationship is indispensable. In the present work, in-situ synchrotron X-ray diffraction was used to investigate the transformation kinetics during Q&P processing. The effect of different heat treatment conditions on the microstructural evolution was examined and correlated to the mechanical properties obtained by tensile testing. The results showed that austenite decomposition occurred for all Q&P cycles, especially at the beginning of partitioning. The extent of this decomposition was affected by a change of the quenching temperature, while the partitioning temperature showed no significant influence. Regardless of the heat treatment parameters, carbon partitioning was clearly visible during the 2-step cycles, which led to enhanced work hardening with increasing strain. In contrast, this was not observed in the case of 1-step processing due to negligible carbon diffusion, and thus insufficient chemical stabilization of the austenite. Graphical abstract: Unlabelled Image Highlights: Transformation kinetics during Q&P heat treatments were studied by HEXRD and correlated with the mechanical properties. Effective carbon partitioning into the austenite during 2-step processing enhanced the strain hardening behavior. Poor austenite stabilization after 1-step processing resulted in low yield strength and high initial strain hardening. More pronounced bainite formation at higher quenching temperature did not affect the mechanical properties.